COUNSELLING GUIDANCE IN ISLAMIC BOARDING SCHOOL: PROBLEM SOLUTION TO STUDENTS’ PERSONALITY [CASE STUDY IN ISLAMIC BOARDING SCHOOL KERTOSONO EAST JAVA] - Fitri Aulia (Universitas Islam Negeri (UIN) Mataram, 2017)
This study tried to open discourse about the availability of guidance and counseling services in the Islamic boarding school, which in this case takes the focus on students of MTs /SMP both are sons and daughters at Islamic Boarding school of Ar-Raudhotul Ilmiah Nganjuk Kertosono of East Java. This research also tried to examine the KCMS, it is a non-test equipment the Guidance and Counseling that arranged for teenagers at Islamic boarding school. Population there were 235 students. Sampel classes VIII and IX MTs sons and daughters. With an error rate of 5% then found the sample of 142 students. Based on the analysis with SPSS version 16 with factor analysis, derived factor 1 include: (a) the problem learning motivation about 77.3%, (b) 74.5% social personality problems (c) Problem 66.0% of religious morality problems, (d) Finance problems about 64.8%, (e) The problem of leisure time about 59.7%, (f) The issue of the opposite sex about 59.6%. Whereas Factor 2 include: (a) physical health problems about 86.9%, (b) technological problems about 69.1%, and (c) Problem families about 41.6%. The rate constancy of this issue serves as a guide in determining the appropriate response. And it would be better if the handling is done directly by the expert of guidance and counseling in order to achieve maximum results.